2018
DOI: 10.1007/s10482-018-1079-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro virulence characteristics of rare serovars of Salmonella enterica isolated from sand lizards (Lacerta agilis L.)

Abstract: The aim of this study was to estimate virulence potential of Salmonella enterica strains colonizing the gut of free-living sand lizards (Lacerta agilis L.). The strains belonged to three Salmonella serovars: Abony, Schleissheim, and Telhashomer. Adhesion and invasion abilities of the strains were determined in quantitative assays using the gentamicin protection method. Induction of apoptosis was assessed using HeLa cell monolayers. PCR assays were used for detection of 26 virulence genes localised within mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
3
1
3
Order By: Relevance
“…S. Schleissheim on the other hand, which was detected in one common buzzard in the present study, is less frequently isolated from environmental samples, 20 mammals including humans, 21,22 birds including a Common buzzard 23 and reptiles 28 (Table 2) in different countries. While animals were not reported to show clinical signs, infection in humans was associated with enteritis.…”
Section: Discussioncontrasting
confidence: 51%
“…S. Schleissheim on the other hand, which was detected in one common buzzard in the present study, is less frequently isolated from environmental samples, 20 mammals including humans, 21,22 birds including a Common buzzard 23 and reptiles 28 (Table 2) in different countries. While animals were not reported to show clinical signs, infection in humans was associated with enteritis.…”
Section: Discussioncontrasting
confidence: 51%
“…The study reported that proteins, such as SiiE (SPI4) were only present in the former while others, such as MgtB (SPI3) and SseL (SPI2) were only in the latter. Similarly, Salmonella characterization from sand lizards showed variations in virulence gene prevalence among rare serovars consequently affecting pathogenicity; serovar Telhashomer, which had no SPI1 genes, also showed the lowest adhesion and apoptosis induction in vitro [ 84 ]. Comparisons between a clinical Salmonella isolate, and two other serovars of different pathogenic potential showed higher disease severity in pigs based on fecal and histopathological scores among the clinical isolate and serovar Typhimurium than Derby, which was reflected accordingly in the absence of some virulence factors in Derby such as lpf , stc , stj , and sodC1 [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chociaż większość serowarów może wywoływać zakażenia wielu gatunków zwierząt, czego najlepszym przykładem jest S. Typhimurium lub S. Enteritidis, niektóre z nich wykazują znacznie mniejszą swoistość w zakresie gospodarza, np. S. Dublin wywołująca głównie zakażenia bydła, S. Choleraesuis typowy serowar dla świń czy S. Gallinarum, którego występowanie jest ograniczone do drobiu (35). Salmonelloza u zwierząt hodowlanych może wystąpić jako infekcja stada z objawami klinicznymi (najczęściej biegunka, gorączka) lub jako postać subkliniczna.…”
Section: Zakażenia Człowiekaunclassified
“…W Nowej Zelandii jaszczurki występujące w popularnych, nadrzecznych terenach wypoczynkowych zidentyfikowano jako źródło licznych zakażeń S. Saintpaul (23). Salmonella, takie jak S. Schleisshem, S. Abony, S. Telhashomer, stwierdzano u wielu osobników rodzimego gatunku jaszczurki zwinki, żyjącego w mieście (35). Badania przeprowadzone w Polsce wykazały, że aż 87,5% węży pochodzących ze środowiska naturalnego było nosicielami Salmonella (60).…”
Section: Zakażenia Człowiekaunclassified